2021
DOI: 10.3389/fimmu.2020.625828
|View full text |Cite
|
Sign up to set email alerts
|

The Sp1-Responsive microRNA-15b Negatively Regulates Rhabdovirus-Triggered Innate Immune Responses in Lower Vertebrates by Targeting TBK1

Abstract: As is known to all, the production of type I interferon (IFN) plays pivotal roles in host innate antiviral immunity, and its moderate production play a positive role in promoting the activation of host innate antiviral immune response. However, the virus will establish a persistent infection model by interfering with the production of IFN, thereby evading the organism inherent antiviral immune response. Therefore, it is of great necessity to research the underlying regulatory mechanisms of type I IFN appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…SP1 is a well-known transcription factor involved in various biological processes. Recently, several studies have reported a role for SP1 in the immune system (42)(43)(44)(45)(46). SP1 is also known to be involved in inflammation, which is an element of the immune system (29, [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…SP1 is a well-known transcription factor involved in various biological processes. Recently, several studies have reported a role for SP1 in the immune system (42)(43)(44)(45)(46). SP1 is also known to be involved in inflammation, which is an element of the immune system (29, [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our study, to avoid nonspecific effects of excessive accumulation of this high molecular weight RNA species on target gene expression, we prolonged the transfection time with miRNA mimics and to study the effect of miRNA on target genes. In teleost fish, many researches have shown that endogenous regulatory molecules miRNAs can regulate the immune response by regulating crucial immune-related genes, such as MITA, IRAK4, TBK1 (54)(55)(56). However, there are few reports on the regulation of RIPK2 by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The expression analysis of miR-122 was executed by using the miRcute miRNA qPCR Detection Kit (Tiangen, Beijing, China). Real-time quantitative PCR (qPCR) was performed in an Applied Biosystems QuantStudio 3 (Thermo Fisher Scientific, Waltham, MA, USA), as we described previously [ 49 ]. The primers for these genes and miRNAs are shown in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…For miRNA target identification, EPC cells and HEK293 cells were cotransfected with wild- or mutant-type MAVS 3′-UTR luciferase reporter, together with MIR122HG or pcDNA3.1. Moreover, to determine the functional regulation of MAVS, EPC cells were cotransfected with NF-κB, Interferon regulatory factor 3 (IRF3), IFN-stimulated response element (ISRE) or type I interferon (IFN-1) luciferase reporter plasmid [ 25 , 49 ], pRL-TK Renilla luciferase plasmid, and MAVS expression plasmid, together with either MIR122HG, MIR122HG-MT or pcDNA3.1, miR-122 mimics or NC, and inhibitors or inhibitor control for dual-luciferase reporter assay. Then, the cells were collected and lysed for reporter activity assays using a dual-luciferase reporter assay system (Promega Madison, WI, USA), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%